2002
DOI: 10.1097/00007890-200209150-00001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ischemia/reperfusion injury and chronic graft deterioration by a single-donor treatment with cobalt-protoporphyrin for the induction of heme oxygenase-1

Abstract: Today, the major problem in organ transplantation is not acute graft rejection but chronic graft deterioration. In addition to alloantigen-specific events, alloantigen independent factors like donor age, previous diseases, consequences of brain death, and perioperative events of ischemia/reperfusion injury have a major impact on long-term graft function. The induction of the stress protein heme oxygenase-1 (HO-1) protects cells from injury and apoptosis. Here, we tested the protective effects of HO-1 induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
3
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(123 citation statements)
references
References 31 publications
7
111
3
2
Order By: Relevance
“…[16][17][18][28][29][30] In most of these studies, the introduction of HO-1 in grafts is achieved by metalloporphyrin (mainly cobalt protoporphyrin), gene transfer or transgenic engineering. These methods need to treat grafts in advance or are limited on transgenic animal models.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][28][29][30] In most of these studies, the introduction of HO-1 in grafts is achieved by metalloporphyrin (mainly cobalt protoporphyrin), gene transfer or transgenic engineering. These methods need to treat grafts in advance or are limited on transgenic animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that cobalt administration ameliorated ischemic injury of the heart (15,25) and the liver (26 -28). In the kidney, Tullius et al (29) showed that treatment with cobalt protoporphyrin improved chronic graft survival of transplant kidneys via induction of heme oxygenase-1. While they attributed improvement in graft survival to prevention of ischemic injury, no detailed information about acute phase of ischemic injury in the kidney was provided, and it remains unclear whether other mechanisms participated in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of HO-1 has previously been shown to protect rats from transplantation-related complications by preventing cytokine responses. 18 We investigated the effect of HO-1 induction by CoPP, or HO repression by SnPP, on liver damage and survival in the cytokine-dependent GalN/ LPS model of apoptotic liver damage. Measurement of plasma ALT revealed that HO-1 induction protected mice from liver injury, while repression of HO increased liver injury (Fig.…”
Section: Ho-1 Induction Protects Mice From Inflammatorymentioning
confidence: 99%